2009
DOI: 10.1002/path.2628
|View full text |Cite
|
Sign up to set email alerts
|

Inactive Wnt/β‐catenin pathway in conventional high‐grade osteosarcoma

Abstract: Osteosarcoma is the most common malignant bone tumour, with a peak incidence in children and young adolescents, suggesting a role of rapid bone growth in its pathogenesis. The Wnt/beta-catenin pathway plays a crucial role in skeletal development and is indispensable for osteoblasts' lineage determination. Previous studies suggesting an oncogenic role for the Wnt/beta-catenin pathway in osteosarcoma were based on cytoplasmic staining of beta-catenin or the detection of one component of this pathway. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
129
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(153 citation statements)
references
References 62 publications
18
129
2
Order By: Relevance
“…At present, the role of Wnt signaling in tumorigenesis of osteosarcoma is under debate. Altogether, the facts that Wnt signaling is required for osteoblastic differentiation, that DKK1 was shown to block the differentiation and increase the transformation of mesenchymal stem cells, and the reported inactivation of the canonical Wnt pathway in osteosarcoma support the conclusion that silencing of the Wnt/β-catenin signaling contributes to tumorigenesis (27)(28)(29). In contrast, inhibition of Wnt signaling by a dominant-negative LRP5 was shown to decrease tumorigenicity and metastasis in osteosarcoma in vivo, and Wnt/β-catenin pathway antagonists such as curcumin and PKF118-310 have been shown to have antitumor effects in osteosarcoma cells, indicating a protumoral role of Wnt signaling (30,31).…”
Section: Discussionmentioning
confidence: 73%
“…At present, the role of Wnt signaling in tumorigenesis of osteosarcoma is under debate. Altogether, the facts that Wnt signaling is required for osteoblastic differentiation, that DKK1 was shown to block the differentiation and increase the transformation of mesenchymal stem cells, and the reported inactivation of the canonical Wnt pathway in osteosarcoma support the conclusion that silencing of the Wnt/β-catenin signaling contributes to tumorigenesis (27)(28)(29). In contrast, inhibition of Wnt signaling by a dominant-negative LRP5 was shown to decrease tumorigenicity and metastasis in osteosarcoma in vivo, and Wnt/β-catenin pathway antagonists such as curcumin and PKF118-310 have been shown to have antitumor effects in osteosarcoma cells, indicating a protumoral role of Wnt signaling (30,31).…”
Section: Discussionmentioning
confidence: 73%
“…Given the crucial role of this pathway in normal osteogenesis (Hartmann, 2006) and tumourigenesis in general, this observation suggests a role for Wnt signalling that differs from that in colorectal cancer, in which upregulation of the pathway is considered to be crucial for tumourigenesis (Klaus and Birchmeier, 2008). Indeed, we have recently shown with a functional reporter assay that Wnt/b-catenin signalling seems to be absent in osteosarcoma cell lines (Cai et al, 2009). In addition, we showed an absence of nuclear b-catenin staining in primary osteosarcomas, indicative of inactive Wnt/ b-catenin signalling.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, GSK3β has been identified as a tumor suppressor that is frequently inactivated in various tumors (42). However, studies have provided evidence that the exact role of GSK3β in tumorigenesis of human OS is controversial (43)(44)(45)(46). In the present study, we explored the effect of ORI on GSK-3β and found that the total GSK-3β protein level was significantly elevated in response to the treatment with ORI.…”
Section: Discussionmentioning
confidence: 79%